Policy instruments for green-growth of clusters: Implications from an agent-based model - Ram Kamath; Zhanli Sun; Frans Hermans (Environmental Innovation and Societal Transitions, 2022)
Green-growth theory asserts that green-innovations will allow us to decouple economic growth from pollution. Policies that promote green-innovations are therefore paramount. Scholarship has become increasingly interested in how green-clusters can contribute to sustainable innovation and decoupled green-growth. In this study, we create an agent-based model that can simulate a cluster's transition, as shaped by different policy instruments. We use this model to explore the effects of a) innovation grants, b) fines for pollution c) financial incentives for entrants, and d) an instrument mix of incentives and fines, on the green-growth of a peripheral-region cluster. Our results indicate that designing instruments for absolutely decoupled growth of peripheral-clusters is close to impossible; and demonstrate the inherent trade-offs in designing policies for relatively decoupled growth. Based on these results, we opine there should be more nuanced deliberation on the potential contribution of green-clusters to sustainable development,with greater focus on the possible trade-offs.
Keywords: 330; decoupling; green-clusters; agent-based modelling; socio-technical transitions; policy instruments